Planning and assessment in higher education : demonstrating insti tutional effectiveness - Middaugh, Michael F., 1945- (San Francisco : Jossey-Bass, 2010)
"This book helps colleges and universities respond to the increasing pressures for accountability by giving them the tools to demonstrate i nstitutional effectiveness. The author is in a unique position to help his colleagues, since he comes at the topic from multiple perspectives, being both a leading practitioner and researcher: Assistant VP for Ins titutional Research and Planning at his university, director of a natio nal research project on costs of instruction, as well as Vice Chair of an accreditation agency. While many books address the issue of assessin g student learning outcomes, this book provides expert guidance for ass essing and promoting institutional effectiveness in supporting student learning. The book's chapters cover every aspect from the overall conte xt of the issue, through measures of effectiveness, to communicating wi th the public, and concludes with a guide to resources"--Provided by pu blisher.
The national context for assessment -- Starting at the beginning: mi ssion-driven planning and assessment -- Assessing institutional effecti veness: student issues -- A core issue in institutional effectiveness: developing sensible measures of student learning -- Maximizing human an d fiscal resources in support of the teaching/learning process -- A com parative context for examining data on teaching loads and instructional costs -- measuring administrative effectiveness -- Communicating asses sment results -- Where do we go from here?
Includes bibliographical references and index.
Keywords: Education, Higher -- Planning; Universities and colleges -- Administration; Education, Higher -- Standards; Education, Higher -- Economic aspects; Educational evaluation; Educational accountability